2019
DOI: 10.14573/altex.1906261
|View full text |Cite
|
Sign up to set email alerts
|

Developing context appropriate toxicity testing approaches using new alternative methods (NAMs)

Abstract: the NAS report, moved forward to outline a broadly collaborative program (Collins et al., 2008) with other United States federal agencies to implement recommendations from the NAS report. A multi-stakeholder program, SEURAT (Safety Evaluation Ultimately Replacing Animal Testing) 1 that focused on implementation of non-animal methods also began in Europe. Following SEURAT, EU-ToxRisk, a large-scale project funded by the European Commission's Horizon 2020 program 2 , is now driving the European research efforts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 61 publications
(74 reference statements)
0
28
0
Order By: Relevance
“…Several theoretical frameworks describing a tiered approach for NGRA have been published over the past few years ( Andersen et al , 2019 ; Berggren et al , 2017 ; Thomas et al , 2019 ), but concrete NGRA examples of how to analyze, integrate and interpret all the data obtained from NAMs to inform a safety decision are still lacking. Therefore, this work represents a milestone in the development and application of nonanimal approaches to assess human safety, showing for the first time that in chemico , in silico , and in vitro approaches can be integrated to arrive at a consumer safety decision for systemic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Several theoretical frameworks describing a tiered approach for NGRA have been published over the past few years ( Andersen et al , 2019 ; Berggren et al , 2017 ; Thomas et al , 2019 ), but concrete NGRA examples of how to analyze, integrate and interpret all the data obtained from NAMs to inform a safety decision are still lacking. Therefore, this work represents a milestone in the development and application of nonanimal approaches to assess human safety, showing for the first time that in chemico , in silico , and in vitro approaches can be integrated to arrive at a consumer safety decision for systemic effects.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental work involved a consecutive, in vitro , longitudinal, and double-blinded study design. The decision criteria method was used for the present investigation ( Andersen et al, 2019 ; Bentz et al, 2013 ). Based on the results obtained in each experiment, it was decided to continue the trials only with those propolis that showed antibacterial activity, antibiofilm and were not cytotoxic to gingival fibroblasts.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental work involved a consecutive, in vitro, longitudinal, and double-blinded study design. The decision criteria method was used for the present investigation (Andersen et al, 2019;Bentz et al, 2013). Based on the results…”
Section: Methodsmentioning
confidence: 99%